Acoustic stimulation during sleep improves cognition and ameliorates Alzheimer's disease pathology in APP/PS1 mice - Shunjie Liu; Su Zhang; Mengxia Guo; Qingfeng Lei; Lu He; Zhong Li (Experimental Gerontology, 2023)
Nonpharmacological therapies for Alzheimer's disease (AD) have become a popular research topic, and acoustic stimulation during sleep is one such promising strategy for the clinical treatment of AD. Some animal experiments have illustrated that acoustic stimulation at a specific frequency can ameliorate AD-related pathology or improve cognition in mice, but these studies did not explore the effective time window of auditory stimulation. Here, we explored the effects of acoustic stimulation during wakefulness and acoustic stimulation during sleep on cognition and AD-related pathology in APP/PS1 mice and the underlying mechanisms. In this study, forty APP/PS1 mice were equally divided into the following 4 groups and treated for 28 days: the chronic sleep deprivation (CSD) group (exposed to sleep deprivation from zeitgeber time [ZT] 0 to ZT 12 each day), the normal sleep and stress exposure (NSS) group (exposed to a stressor from ZT 0 to ZT 12 each day), the acoustic stimulation during wakefulness (ASW) group (exposed to sleep deprivation and 40 Hz acoustic stimulation from ZT 0 to ZT 12 each day) and the acoustic stimulation during sleep (ASS) group (exposed to sleep deprivation from ZT 0 to ZT 12 and 40 Hz acoustic stimulation from ZT 12 to ZT 24 each day). After the intervention, cognition was assessed by behavioural experiments. The amyloid-β burden was analysed by Western blotting, immunofluorescence and enzyme-linked immunosorbent assay. Tau pathology was assessed by Western blotting. Mitochondrial function was evaluated by transmission electron microscopy, Western blotting and fluorescence intensity measurement. We found that the NSS and ASS groups had better cognitive functions than the CSD and ASW groups. The Aβ burden and tau phosphorylation were lower in the NSS and ASS groups than in the CSD and ASW groups. Mitochondrial function was better in the NSS and ASS groups than in the CSD and ASW groups. However, the differences in these parameters between the NSS and ASS groups and between the CSD and ASW groups were not significant. Our findings suggest that acoustic stimulation at a specific frequency during sleep, but not during wakefulness, reduces the amyloid-β burden by inhibiting amyloid beta precursor protein-binding protein 2, hinders tau phosphorylation by blocking glycogen synthase kinase 3 beta, and restores mitochondrial function by elevating mitophagy and promoting mitochondrial biogenesis.